Dampak Revolusi AI terhadap Integritas Mahasiswa UIN Imam Bonjol dalam Pendidikan Formal - Zalia, Dela; Safitria, Zelda; Gusmaneli, Gusmaneli (Lembaga Yasin AlSys, 2025)
The Industrial Revolutions 4.0 and 5.0, marked by advances in Artificial Intelligence (AI), have introduced new challenges to students’ academic integrity, particularly within UIN Imam Bonjol Padang, which is grounded in Islamic values. This study aims to holistically examine how students confront ethical dilemmas in AI usage and to assess how their scientific integrity is tested and shaped through the internalization of the values of amanah, sidq, and istiqamah. A descriptive qualitative approach with an intrinsic case study design was employed, involving students, lecturers, and academic administrators through semi-structured interviews, academic documentation, and limited observation. The findings indicate that AI plays a dual role: on one hand, it supports learning efficiency and personalization; on the other, it poses risks of plagiarism and a decline in critical thinking motivation. Within the UIN Imam Bonjol context, Islamic values have proven to be a vital foundation in preserving and shaping students’ academic integrity amidst technological disruption. The study concludes by emphasizing the urgency of value-based education and character development as essential counterparts to technological advancement. The implications encourage Islamic higher education institutions to develop ethically grounded curricula and digital literacy strategies so that AI serves as a tool for character reinforcement rather than erosion.